Consciousness modeled: reification and promising pluralism - Grønfeldt Winther, Rasmus (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
A tremendous opportunity lies in store for those of us interested in consciousness.I here bracket the arguments of those who wish to minimize or reduce consciousnessaway, either up into socially-based discourses and institutional power (e.g., Luhmannor Foucault) or down into sheer neural patterns (e.g., Paul Churchland). [...]